MUCOADHESIVE BUCCAL FILMS: A NOVEL APPROACH FOR THE DELIVERY OF ANTI-HYPERTENSIVE DRUGS - YELAVE, ADESH; GEETA BHAGWAT (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The buccal drug delivery system is a prominent route of administration for drug delivery through the buccal mucosa. It is rich in blood supply with more surface area for rapid absorption as well as provides direct entry of drugs from the site of application into the systemic circulation through the jugular vein. Buccal drug delivery systems consist of various approaches such as lozenges, wafers, gels, microparticles, patches or films from which mucoadhesive buccal film is an attractive dosage form in terms of flexibility and high systemic bioavailability. Since most of the antihypertensive drugs show first-pass metabolism which leads to less oral bioavailability generally up to 20–50%. Thus, incorporation of antihypertensive drugs in mucoadhesive buccal films using mucoadhesive polymers can provide higher systemic bioavailability. The films can be formulated using various techniques such as solvent casting method and hot extrusion melt method. These films can be evaluated based on various characteristics to determine their efficacy and performance such as tensile strength, mucoadhesion residence time, and kinetic release data analysis. They have various advantages over conventional solid oral dosage forms, hence are preferable for the preparation of antihypertensive drug-loaded buccal films. Mucoadhesive buccal films of antihypertensive drugs can also provide controlled drug delivery with enhanced bioavailability.